A New Paradigm in Cardiac Regeneration: The Mesenchymal Stem Cell Secretome - Clara Gallina; Valentina Turinetto; Claudia Giachino (Stem Cells International)
The potentialities to apply mesenchymal stem cells (MSCs) in regenerative medicine have been extensively studied over the last decades. In the cardiovascular disease (CVD) field, MSCs-based therapy is the subject of great expectations. Its therapeutic potential has been already shown in several preclinical models and both the safety and efficacy of MSCs-based therapy are being evaluated in humans. It is now clear that the predominant mechanism by which MSCs participate in heart tissue repair is through a paracrine activity. Via the production of a multitude of trophic factors endowed with different properties, MSCs can reduce tissue injury, protect tissue from further adverse effects, and enhance tissue repair. The present review discusses the current understanding of the MSCs secretome as a therapy for treatment of CVD. We provide insights into the possible employment of the MSCs secretome and their released extracellular vesicles as novel approaches for cardiac regeneration that would have certain advantages over injection of living cells.